Personalizirana kozmetika na slovenskem trgu - Doler, Ajda (Farmacevtski vestnik, 2023)
Personalized cosmetics are a developing trend in the cosmetics industry and may include a personalised formulation (ingredients, textures, fragrances) or packaging. The production and development of personalised cosmetics are based on the use of modern technologies, especially artificial intelligence. Important steps in the production of personalised cosmetic products are obtaining data about the consumer, the analysis of the obtained data, and the production and delivery of a final product to the consumer. Unlike conventional cosmetics, in the case of personalised cosmetic products, the consumer is a very important element already in the product manufacturing step. In this article, we researched how personalised cosmetics are represented on the Slovenian market. We analysed 67 personalised cosmetic products and found that in Slovenia, the most accessible personalised products have a personalised formulation. Among personalised products, most of them are skin care products, which are also the most expensive on average. In most cases, manufacturers obtain data from consumers using an online survey, which is most often analysed using algorithms. The majority of personalised cosmetic products are made in a classic production facility.
Keywords: Kozmetika; personalizacija; personalizirana kozmetika; potrošnik; slovenski trg; umetna inteligenca